NK cell-mediated immunostimulatory effects of ethanol extract of Morinda citrifolia (noni) fruit - Haeyeop Kim; Laily Rahmawati; Yo Han Hong; Su-Young Choi; Jae Youl Cho (BMC, 2022)
Abstract Background Morinda citrifolia (Noni) is a plant that has long been used in various products such as foods and cosmetics. Although noni has been known to have immunostimulatory activity, detailed mechanism at the cellular level has not been fully elucidated yet. In this study, we focused on understanding as to how noni fruit can positively stimulate body's immune responses. Methods To do this, an ethanol extract of noni fruit (Mc-fEE) was prepared and administered for 30 days to male C57BL/6 mice for in vivo experiment. NK cell activity and cytokine production level from Mc-fEE-treated mice were analyzed by flowcytometry, real-time PCR, and ELISA. Mc-fEE-triggered molecular events were detected from RAW264.7 cells and splenocytes using Western blotting and real-time PCR analyses. Results The mRNA expression levels of cytokines such as interleukin families, interferon (IFN)-β, and tumor necrosis factor (TNF)-α were increased by Mc-fEE treatment in vitro and in vivo. Western blotting analysis showed that the phosphorylation levels of nuclear factor (NF)-κB and activator protein (AP)-1 subunits these were enhanced in Mc-fEE-treated RAW264.7 cells. In addition, according to in vivo experiments, it was considered that Mc-fEE can increase the population of splenic NK cells and subsequent upregulation of their cytotoxic activity against YAC-1 cells, a T- cell lymphoma. Conclusion In this paper, we could confirm that Mc-fEE has remarkable immunostimulatory effects by activation and increase of the NK cell population.